LEADERSHIP, NETWORK INNOVATION AND INNOVATION LABORATORIES: AN EPISTEMOLOGICAL ANALYSIS (ADMPG Journal, 2025)
This study performs epistemological and sociological analyzes to provide a multidimensional understanding of the themes of leadership, network innovation and innovation laboratories, based on a literature review and the choice of representative articles. The selected authors — Tõnurist, Kattel, Lember, Puttick, and Rodríguez and Grandinetti — were chosen due to their substantial contributions and varied perspectives on innovation in the public sector. The epistemological analysis identifies how specific methodologies and theories influence the authors' approaches, revealing an intersection of empiricism, rationalism, functionalism and constructivism, illustrating the complexity of the field. On the other hand, sociological analysis highlights how authors' cultural backgrounds and contexts shape their perspectives and approaches. The research reveals the need for integrated approaches that consider both theories and practices, and suggests an expansion of studies on leadership and public innovation in Brazil, where cultural and institutional particularities can offer new perspectives on the topic.